Exploring the Treasure of Plant Molecules With Integrated Biorefineries - Torres, Andres F.; Xu, Xuan; Nikiforidis, Constantinos V.; Bitter, Johannes H.; Trindade, Luisa M. (Frontiers in Plant Science, 2019)
Despite significant progress towards the commercialization of biobased products, today’s biorefineries are far from achieving their intended goal of total biomass valorization and effective product diversification. The problem is conceptual. Modern biorefineries were built around well-optimized, cost-effective chemical synthesis routes, like those used in petroleum refineries for the synthesis of fuels, plastics and solvents. However, these were designed for the conversion of fossil resources and are far from optimal for the processing of biomass, which has unique chemical characteristics. Accordingly, existing biomass commodities were never intended for modern biorefineries as they were bred to meet the needs of conventional agriculture. In this perspective paper we propose a new path towards the design of efficient biorefineries which capitalizes on a cross-disciplinary synergy between plant, physical and catalysis science. In our view, the best opportunity to advance profitable and sustainable biorefineries requires the parallel development of novel feedstocks, conversion protocols and synthesis routes specifically tailored for total biomass valorization. Above all, we believe that plant biologists and process technologists can jointly explore the natural diversity of plants to synchronously develop both, biobased crops with designer-chemistries and compatible conversion protocols which enable maximal biomass valorization with minimum input utilization. By building biorefineries from the bottom-up (i.e., starting with the crop), the envisioned partnership promises to develop cost-effective, biomass-dedicated routes which can be effectively scaled-up to deliver profitable and resource-use efficient biorefineries.